Debates over the Slovene Language and Its Influence on the Shape of Slovene Literature in the Romantic Period - Gruda, Marlena (Poznańskie Studia Slawistyczne, 2023)
The article aims to explore the status of the Slovene language and literature, as well as Slovene culture during the Romantic period in the context of historical events which informed them as a result of the creation of the alphabet by Adam Bohorič in the 16th century. During the 19th century, in Slovenia an “orthographic war” was being waged. Its goal was to establish the one and correct version of the alphabet and the definitive spelling rules for the Slovene language. The debate about language erupted between the group under the leadership of Matia Čop (of which France Prešeren was a member) and the followers of Jernej Kopitar. The dispute involved a number of issues connected to Slovene literature and culture, and the status of Slovenia in Europe. Arguments in the debate were exchanged via publications, (e.g. Slovenska abecedna vojska), poetry (Satirical Sonnets and epigrams) and engaged a wide spectrum of topics such as the dialects of the Slovene language or literary criticism.